Synthesis of co-deposited hexagonal boron nitride for thermally-efficient tribological performance - Bello, Kamilu Adeyemi; Maleque, Md. Abdul; Ahmad, Zuraida; S. , Mirdha (Trans Tech Publications, Switzerland, 2015)
Research in the area of alloyed deposition on ceramic particles is gaining widespread acceptance in tribology community to produce advanced wear-resistance surfaces by environmentally acceptable coating technologies. In this study, autocatalytic electroless deposition technique was used to incorporate hexagonal boron nitride (hBN) lubricant particles in nickelphosphorous matrix. The substrate particles were subjected to series of pretreatment operations prior to electroless co-deposition process. Surface morphology and composition of pure hBN and treated powders were characterized by means of scanning electron microscopy (SEM), energy dispersive x-ray (EDX) and field emission scanning electron microscopy (FESEM). The results revealed that the pretreated particles have rough and increased surface area that aided deposition process. It was also found that uniform Ni-P alloy layer was successfully synthesized on Ni-coated hBN powder. Thus, the developed electroless co-deposited hBN composite powder may be regarded as an advanced solid lubricant material coating which may either be directly applied on the sliding mating surfaces or deposited by laser-cladding, TIG torch melting or thermal spaying, etc to improve the surface properties of metallic substrates against wear and friction for high temperature applications.